Pre-codification and equalization schemes for hybrid sub-connected architectures in the millimeter wave band - Simões, Ricardo Simões de (2019)
In the last years, the demand for high data rates increased substantially and the mobile communications are currently a necessity for our society. Thus, the number of users to access interactive services and applications has increased. The next generation of wireless communications (5G) is expected to be released in 2020 and it is projected to provide extremely high data rates for the users. The millimeter wave communications band and the massive MIMO are two promising keys technologies to achieve the multi Gbps for the future generations of mobile communications, in particular the 5G. The conjugation of these two technologies, allows packing a large number of antennas in the same volume than in the current frequencies and increase the spectral efficiency. However, when we have a large number of antennas, it is not reasonable to have a fully digital architecture due to the hardware constrains. On the other hand, it is not feasible to have a system that works only in the analog domain by employing a full analog beamforming since the performance is poor. Therefore, it is required a design of hybrid analog/digital architectures to reduce the complexity and achieve a good performance. Fully connected and sub-connected schemes are two examples of hybrid architectures. In the fully connected one, all RF chain connect to all antenna elements while in the sub-connected architecture, each RF chain is connected to a group of antennas. Consequently, the sub-connected architecture is more attractive due to the low complexity when compared to the fully connected one. Also, it is expected that millimeter waves be wideband, however, most of the works developed in last years for hybrid architectures are mainly focused in narrowband channels. Therefore, in this dissertation it is designed a low complex analog precoder at the user terminals and a hybrid analog-digital multi-user linear equalizer for broadband sub-connected millimeter wave massive MIMO at the base station. The analog precoder at the transmitter considers a quantized version of the average angle of departure of each cluster for its computation. In order to remove the multi-user interference, it is considered a hybrid sub-connected approach that minimizes the bit error rate (BER). The performance results show that the proposed hybrid sub-connected scheme is close to the hybrid full-connected design. However, due to the large number of connections, the full-connected scheme is slightly better than the proposed sub-connected scheme but with higher complexity. Therefore, the proposed analog precoder and hybrid sub-connected equalizer are more feasible to practical applications due to the good trade-off between performance and complexity.